An efficient method for indexing grazing‐incidence X‐ray diffraction data of epitaxially grown thin films. Issue 3 (2nd April 2020) - Simbrunner, Josef; Schrode, Benedikt; Domke, Jari; Fritz, Torsten; Salzmann, Ingo; Resel, Roland
Abstract : A method is described for indexing grazing‐incidence X‐ray diffraction data of epitaxially grown thin films comprising various crystal orientations and/or polymorphs by measuring reciprocal‐lattice vectors. Abstract : Crystal structure identification of thin organic films entails a number of technical and methodological challenges. In particular, if molecular crystals are epitaxially grown on single‐crystalline substrates a complex scenario of multiple preferred orientations of the adsorbate, several symmetry‐related in‐plane alignments and the occurrence of unknown polymorphs is frequently observed. In theory, the parameters of the reduced unit cell and its orientation can simply be obtained from the matrix of three linearly independent reciprocal‐space vectors. However, if the sample exhibits unit cells in various orientations and/or with different lattice parameters, it is necessary to assign all experimentally obtained reflections to their associated individual origin. In the present work, an effective algorithm is described to accomplish this task in order to determine the unit‐cell parameters of complex systems comprising different orientations and polymorphs. This method is applied to a polycrystalline thin film of the conjugated organic material 6, 13‐pentacenequinone (PQ) epitaxially grown on an Ag(111) surface. All reciprocal vectors can be allocated to unit cells of the same lattice constants but grown in various orientations [sixfold rotational symmetry for the contact planes (102) and (1 02 )]. The as‐determined unit cell is identical to that reported in a previous study determined for a fibre‐textured PQ film. Preliminary results further indicate that the algorithm is especially effective in analysing epitaxially grown crystallites not only for various orientations, but also if different polymorphs are present in the film.